Detection Time of Oxazepam and Zopiclone in Urine and Oral Fluid after Experimental Oral Dosing. Issue 5 (7th January 2019) - Bruun, Lina Dorthea; Kjeldstadli, Kari; Temte, Vidar; Birdal, Morris; Bachs, Liliana; Langødegård, Marit; Strand, Dag Helge; Gaare, Kristin Irene; Øiestad, Elisabeth; Høiseth, Gudrun
Abstract: Data from previous experimental studies on the detection time of oxazepam and zopiclone in biological matrices are limited. The aim of this study was to examine the detection time in urine and oral fluid after single oral doses of oxazepam and zopiclone. Ten healthy volunteers received 25 mg of oxazepam in the evening of Day 1 and 7.5 mg of zopiclone in the evening of Day 3. Urine and oral fluid samples were collected twice daily for 9 days, with an additional sampling the day after ingestion of zopiclone. A total of 19 samples of both urine and oral fluid from each participant were analyzed using fully validated chromatographic methods. The median detection time for oxazepam was 91 h (range 73–108) in urine and 67 h (range 50–98) in oral fluid. The median detection time for zopiclone in urine was 49 h (range 25–98) and 59 h (range 48–146) in oral fluid. The metabolite zopiclone N-oxide showed a detection time of 36 h (range 25–84) in urine. The area under the concentration–time curve (AUCTotal ) in urine corrected for creatinine was 150 μmol/L/mmol/L*h (range 105–216) for oxazepam and 1.60 μmol/L/mmol/L*h (range 0.79–4.53) for zopiclone. In oral fluid, the AUCtotal was 673 nmol/L*h (range 339–1, 316) for oxazepam and 2, 150 nmol/L*h (range 493–4, 240) for zopiclone. In conclusion, oxazepam can be detected longer in urine than in oral fluid, while zopiclone can be detected longer in oral fluid than in urine. The high AUCTotal for zopiclone in oral fluid shows that the transfer into oral fluid is significant. In certain individuals the detection time of zopiclone in oral fluid is long. These results can be helpful when interpreting drug testing analyzes.